2007
DOI: 10.2320/matertrans.mj200744
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior of Ca-Based Bulk Amorphous Materials

Abstract: In this study, the room-temperature oxidation behaviors of three Ca-based bulk amorphous alloys, Ca 65 Mg 15 Zn 20 , Ca 50 Mg 20 Cu 30 , and Ca 55 Mg 18 Zn 11 Cu 16 , were examined under normal flowing laboratory air and compared with the oxidation behaviors of these alloys in the crystalline form under identical conditions. The degree of oxidation for alloys in the amorphous and crystalline conditions was investigated by periodically measuring the mass change over the oxidation time. From the results of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…The ternary Ca-Mg-Zn and Ca-Mg-Cu glassy alloys also have marginal oxidation and corrosion resistance. [13][14][15] Quaternary Ca-Mg-Zn-Cu BMGs have better oxidation and corrosion resistance, which improves even further with addition of Al. [15] Partial substitution of Cu or Zn with Al also reduces the density of these alloys.…”
Section: Low Density Bulk Metallic Glasses (Bmgs) Inmentioning
confidence: 97%
“…The ternary Ca-Mg-Zn and Ca-Mg-Cu glassy alloys also have marginal oxidation and corrosion resistance. [13][14][15] Quaternary Ca-Mg-Zn-Cu BMGs have better oxidation and corrosion resistance, which improves even further with addition of Al. [15] Partial substitution of Cu or Zn with Al also reduces the density of these alloys.…”
Section: Low Density Bulk Metallic Glasses (Bmgs) Inmentioning
confidence: 97%
“…Cu 16 , was examined under normal flowing laboratory air and compared with the oxidation behaviors of these alloys in crystalline form under identical conditions. [26] The dependences of net mass change due to oxide formation per unit surface area, W, on the oxidation time, t, are presented in Figures 9(a) through (c) for amorphous and crystalline specimens. For each alloy, oxidation occurs at a faster rate in the crystalline condition than in the amorphous condition.…”
Section: Compression Propertiesmentioning
confidence: 99%
“…[62] The results are shown in Figure 10. Ternary Ca-Mg-Zn and Ca-Mg-Cu BMGs experienced destructive corrosion reactions, resulting [26] in a net loss of mass from the samples due to spallation of the corrosion products. The weight loss of Ca 65 Mg 15 Zn 20 BMG occurred immediately after immersion in water, but the rate of the weight loss continuously decreased with time, reached a minimum after about 400 hours of holding, and then suddenly increased again, leading to a second cycle of corrosion that was similar to the first cycle; after~700 hours of holding in water, the sample lost about 65 pct of its mass (Figure 10(a)).…”
Section: Compression Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The amorphous state considerably improves the oxidation and corrosion resistance of these alloys, although these properties also depend on the alloy constitution. [21][22][23] For example, recent studies of four Ca-Mg-Zn, Ca-Mg-Cu, Ca-Mg-Zn-Cu and Ca-Mg-Al-Zn-Cu metallic glasses have shown that the ternary Ca-Mg-Zn glass has the least oxidation and corrosion resistance. Substitution of Zn with Cu and/or Al improves these properties, and the alloy containing Al has the best corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%